Ultrasonic pulse propagation simulation using OpenCL for environment mapping and discovery. (September 2019) - Al-Shorman, Mohammad Y; Al-Kofahi, Majd M
A fast, highly parallelized, simulation of unidirectional ultrasonic pulse propagating in a two-dimensional environment is presented. The pulse intensity versus time is recorded using an array of unidirectional ultrasonic receivers located at known locations and arranged in a small circle around the transmitter. To speed up the simulation process, OpenCL 2.0 heterogeneous compute language on a graphics processing unit is used. The simulation result is then compared with experimental data to validate its accuracy. By comparing both simulated and experimental data, the collected intensity–time profiles can be used to map an environment. Environments can be mapped using not only direct reflections but also higher order reflections from objects that are not directly seen by the transmitter. With the help of this simulation, subtle characteristics in an environment, such as a slight tilt or curvature, can be measured. The front end of the simulation is written using C#, while the back end is written using C\C++ and OpenCL.